Deciphering oligomeric proanthocyanidins’ dual osteoprotective mechanisms at single-cell resolution: NR4A1-mediated PTGS2 suppression and β-catenin-Runx2 activation - Huang, Li; Sun, Yuwei; Zheng, Yi; Qiu, Shicheng; Zheng, Jianping; Sun, Chunhan; Chen, Mingwei; Zheng, Shaowei; Zeng, Yirong (Frontiers in Immunology, 2025)
BackgroundOsteoporosis (OP), as a systemic bone disorder, has a complex pathogenesis and faces significant challenges in clinical treatment. Oligomeric proanthocyanidin (OPC), a type of natural polyphenolic flavonoid compound, demonstrates outstanding therapeutic potential due to its excellent antioxidant and anti-inflammatory properties and good safety. The breakthrough advances in single-cell RNA sequencing (scRNA-seq) technology have provided a powerful research tool for elucidating the multitarget mechanisms of OPC in the treatment of OP.MethodsThis study first screened the active components of OPC leveraging the TCMSP database. The protein–protein interaction network of OPC target proteins was generated through the STRING database, and visual analysis was accomplished using the Cytoscape software. The ClusterProfiler R package and ClueGO plugin were employed for functional enrichment analysis and network visualization. At the same time, scRNA-seq data from the GEO database were integrated, and cell-type identification was attained using the Seurat tool. The differentiation trajectories of subtypes were inferred using Monocle and Slingshot software. The cell communication network was analyzed using CellChat.ResultsThis study utilized scRNA-seq to identify C2 NR4A1+ MSCs with distinct metabolic features and differentiation potential in the bone microenvironment during the early stage of OP, namely, osteopenia. The natural component OPC can precisely target this subtype and exert therapeutic effects through two mechanisms: inhibiting the transcriptional activity of NR4A1 to suppress the expression of PTGS2 in MSCs and simultaneously activating the β-catenin-dependent NR4A1–Runx2 signaling axis to promote osteogenesis and inhibit osteoclastogenesis. These findings establish a new therapeutic paradigm of “targeting cell subtypes–multipathway regulation,” providing an important basis for the development of novel anti-OP drugs.ConclusionOur research integrated multilevel approaches, including single-cell transcriptomics, network pharmacology, cellular experiments, and animal models, to systematically reveal the dual mechanism of OPC in treating OP. This discovery not only established C2 NR4A1+ MSCs as key mediators in the pathological process of OP but also clarified the molecular mechanism of multitarget synergy of natural active compounds in restoring bone homeostasis, providing a theoretical basis and practical guidance for the development of new OP therapies.